Step 1: subtract x from -3. New equation should be y=-3-x. Step 2: plug that equation into top equation. Should be 5x + 2(-3-x) = 9. Step 3: use distribitive properties on 2(-3-x). New equation is 5x - 6 - 2x = 9. Step 4: combine like terms. New equation 3x - 6 = 9. Step 5: work it out. Divide 3x and 9 by 3. New equation is x - 6 = 3. Add 6 to -6 and 9. Final eqaution is x = 9. Step 6: swap 9 for x in second equation. New equation is 9 + y = -3 Step 7: subtract 9 from 9 and -3. New equation is y = -12 : = = -